NET BENEFIT ANALYSIS TO THE REFERENT GROUP TERHADAP DAMPAK IMUNITAS HUKUM APARAT PENEGAK HUKUM DI INDONESIA - Sugianto, Fajar (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2016)
Net Benefit Analysis (NBA) is a technique aimed at identifying the least costly way of achieving a given objective. It weights the expected benefits of choices or policy against its expected costs. The difference between the anticipated benefits and the anticipated costs is then used to choose among competing alternatives. In this writing, benefits are approximated by a willingess to pay, while costs are formalized either as a willingness to pay to avoid or, alternatively, as opportunity costs. It also shows that NBA does not require the expression of benefits and costs in money terms. The result of this analysis provides a choice among alternative means and address the preliminary question of whether the end is worth pursuing, or which among alternative goals should be pursued.